Identifikasi dan Analisis Kualitatif Risiko Sistem E-Budgeting dan E-Procurement Studi Kasus: Administrasi Pembangunan Pemerintah Kota Surabaya - Theresia Lulu Indah Kurniawati; Mochamad Chandra Saputra; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-government refers to the using of government agencies with information technology (internet, mobile computing, WAN) that has abilities to change relationships between citizens, business people and other government executives. Advantages of using e-government is increased transparency of information for residents of Surabaya. This research is used to identify risks in the application of e-budgeting and e-procurement systems managed by Administrasi Pembangunan which has been used for more than 10 years. The risk identification process in this study refers to the risk management techniques which is described by the PMBOK 5th edition (Project Management Body of Knowledge) and Pritchard in Risk Management Concepts and Guidance 5th edition. Risk management in this research is used for reviewing risks that may occur of the system. Risk management in this research uses expert judgment and rating schemes method. The result of using expert judgment method is, there are six risks faced by Administrasi Pembangunan: inflation, integration problem, human resource productivity, infrastructure, system development and short term employee. The result of qualitative analysis using rating schemes method is, there are seven high risk, four medium risks and one low risks.